Digitalization in the construction industry and its impacts on productivity: an empirical investigation of the South African construction industry - Nxumalo, Mhlonipheni Darlington (Department of Construction Economics and Management, 2026)
This study investigates the role of digitalization in the construction sector and its impacts on productivity, with a specific focus on the South African construction industry. Employing a quantitative research approach, data was collected using survey research design through close-ended questionnaires. A non-probability sampling method with both quota and convenience sampling techniques was used to select a sample of 200 participants to examine the relationships among digitization, digitalization concepts, digital transformation, and organizational productivity. Data was collected with a 17-item Digital Transformation Scale (DTS) adapted from Pettersson, Siljebo, Wolming, and Ferry (2024) consisting of three dimensions of digitalization (6 items), digitization (5 items) and digital transformation (6 items) and a 12-item Organizational Effectiveness Inventory (OEI) adapted from Szumal (2001) with three dimensions of organization level quality (6 items), departmental level quality (3 items) and external adaptability (3 items) was used to tap perceptions of organizational performance. The analysis incorporated reliability tests, descriptive statistics, correlation analysis, and regression modeling to identify significant trends and impacts. Hypothesis testing yielded essential insights into the relationships among the constructs. The size of an organization significantly affects perceptions of digitalization and productivity within the South African construction sector. ANOVA results indicate that larger organizations exhibit significantly elevated levels of composite digitalization and organizational performance. Marked disparities are apparent in areas such as departmental performance, overall performance, and adaptability, with smaller firms lagging due to limitations in resources and capabilities. The ANOVA results indicated that organizations with a higher number of years in business have significantly higher levels of composite digitalization. Digitalization was found to have a positive significant effect on organizational productivity, results also show digitization to have a positive significant effect on organizational productivity and digital transformation tools exhibited no significant impact. Composite digitalization showed a strong and significant positive effect on productivity highlighting the importance of an integrated and comprehensive approach to digitalization. The significance of this based on the need to the fill the critical knowledge gap in the academia regarding the impact of digitalization on productivity in the South African construction industry. Its findings inform the strategic decisions, drive innovation, and the approaches for efficient and competitive construction sector in South Africa.